The Role of Evil in Edgar Allan Poe's Short Stories - Macháčková, Tereza (Univerzita Pardubice, 2019)
The thesis deals with the role of evil in Edgar Allan Poe's short stories. The main points of the thesis are demonstrated on three short stories, The Imp of Perverse, The Cask of Amontillado and The Hop Frog. It analyses the behavior and personality of the main characters, the results of the analysis based on the philosophical view of evil and literary context and characterization of the genre.
Role zla v díle Edgara Allana Poea
Keywords: Poe, Edgar Allan; zlo; americká gotika; gotický román; Poe, Edgar Allan; evil; American Gothic; Gothic novel